Implementasi dan Akibat Hukum Perjanjian Perkawinan Setelah Keluarnya Putusan MK NO.69/PUU-XIIX/2015 - Suhaila Zulkifli (Universitas Islam Sumatera Utara, 2018)
AbstractThe marriage agreement is marriage planning, and each couple is entitled to prepare it. The marriage agreement serves is a preparation for living a home life to minimize and to avoid a dispute between husband and wife, and to provide legal certainty between the rights and obligations of each party. In the Marriage Law No. 1 of 1974, Article 29 Paragraph (1) states that the Marriage Agreement must be executed when or before the marriage takes place; by the enactment of the Constitutional Court Decision No. 69 / PUU-XIII / 2015, the phrase